Optimalisasi Pengembangan Digitalisasi Marketing Dan Digital Branding Produk UMKM Madu Lebah Klanceng - Amanda Amelia Sari; Acep Samsudin (Pusat Riset dan Inovasi Nasional, 2023)
The utilization of information technology has expanded into the realm of digital marketing for entrepreneurs. There are numerous ways in which this technology is adopted as an accelerator in business processes, and one of them is through the utilization of digital media. Digital marketing, which is a product of information technology, encompasses the promotion of products and/or services through social media. One of the challenges faced by micro, small, and medium enterprises (MSMEs), particularly Madu Lebah Klanceng, an MSME located in Talang Village, is their reliance on conventional promotion methods such as distributing brochures, participating in bazaars, setting up stalls, and word-of-mouth promotion. This limits the reach of their marketing and sales efforts, impeding the rapid growth of their business. To achieve the goals of digital branding and digital marketing, training and mentoring sessions are conducted through the delivery of materials, discussions, and practical exercises on digital branding and marketing techniques. The method used is qualitative, involving data collection through observations, interviews, and documentation of the activities carried out by the MSMEs. It is hoped that through these activities, MSME entrepreneurs will gain a better understanding of the importance of utilizing internet media to build their brand and enhance their marketing efforts.